2016
DOI: 10.4172/2165-7890.1000178
|View full text |Cite
|
Sign up to set email alerts
|

An Abnormal Cerebellar Network in Children with Autistic Spectrum Disorder: A Morphometric Study

Abstract: Autism is a neurodevelopmental disorder characterized by poor social abilities, communication deficiency and restricted behavioural patterns. Recently, scholars started to consider the possibility of detecting biological markers for better and faster diagnosing autism. This problem has been approached from different perspectives considering biochemical, neurophysiological, and neuroanatomical markers. Following this perspective, our intent was to investigate whether a structural brain signature of autism can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
(43 reference statements)
2
6
0
Order By: Relevance
“…SoBM is an innovative approach to study the neural abnormalities in autism. As a multivariate data‐driven method, it exploits independent component analysis (ICA) to extract clusters of GM covarying between participants as structural networks not defined a priori (Xu et al ., ; Grecucci et al ., ; Pappaianni et al ., ). On the other hand, VBM is a univariate method that allows to find out relevant differences in GM concentration with a direct comparison in terms of clusters of voxels in the brain between groups.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…SoBM is an innovative approach to study the neural abnormalities in autism. As a multivariate data‐driven method, it exploits independent component analysis (ICA) to extract clusters of GM covarying between participants as structural networks not defined a priori (Xu et al ., ; Grecucci et al ., ; Pappaianni et al ., ). On the other hand, VBM is a univariate method that allows to find out relevant differences in GM concentration with a direct comparison in terms of clusters of voxels in the brain between groups.…”
Section: Discussionmentioning
confidence: 97%
“…They also found that the entity of GM abnormalities correlated with social and behavioural deficits as manifested by ASD. Another study tried to extend these results on younger children between 6 and 12 years old (Pappaianni et al ., ). They found a significant network including several cerebellar regions (as inferior semilunar lobule, tuble, uvula, pyramis, declive and cerebellar tonsil) and the fusiform gyrus.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite the notable results, the conclusions of these studies are limited because most of them have compared SZ and BD only indirectly by analyzing each group of patients with respect to healthy controls (Mcintosh et al, 2004; Farrow et al, 2005; Arnone et al, 2009; Yu et al, 2010; Ellison-Wright and Bullmore, 2010). Moreover, an important methodological limitation is due to the use of univariate methods (such as VBM) to investigate large-scale networks that are involved in psychiatric disorders (Pappaianni et al, 2017; Pappaianni and Grecucci, 2016), since such methods do not consider the relation between different voxels in a whole brain fashion (Xu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…All these 1112 datasets collected MRI (functional and structural) and phenotypic information for each subject. The ABIDE website is http://fcon_1000.projects.nitrc.org/indi/abide/ which describes the scan procedures and parameters [3] [8]. The data available in the website is based on considerable variation SMRI acquisition protocols across sites and from the data of children and adolescents from three participating institutions.…”
Section: Resultsmentioning
confidence: 99%